The Imensity of Being Singular Approaching Migrant Lives in São Paulo through Resonance - Toji, Simone (HAU Books, 2023)
In this powerful new work, Simone Toji reconsiders ethnography as a form of appreciation of the contradictions inherent in the making of life itself. Recovering Bronislaw Malinowski's idea of the "imponderabilia of actual life" as an inspiring ethnographic attitude, she shows how lives are composed through moments of indecision, opacity, and incongruity that make them irreducibly open ended. The singular lives of four migrants, from Paraguay, South Korea, and Bolivia, are rendered as journeys across the city of São Paulo, interspersed with resonant explorations of the power of life's invention and reinvention as part of the human condition. This important new book is a major contribution to migration studies, social and cultural anthropology, and the social sciences as a whole, and will appeal to readers from the undergraduate level through the doctoral.